2017
DOI: 10.1186/s13075-017-1277-1
|View full text |Cite
|
Sign up to set email alerts
|

Minimal disease activity and impact of disease in psoriatic arthritis: a Spanish cross-sectional multicenter study

Abstract: BackgroundPatients with psoriatic arthritis (PsA) experience functional impairment and reduced quality of life, and thus patient global assessment in PsA is explained mainly by the physical, but also by the psychological, aspect of the disease. To assess the prevalence of minimal disease activity (MDA) in Spanish patients with PsA, we examined their characteristics and the association between MDA and the impact of the disease as assessed by the PsA Impact of Disease (PsAID) questionnaire.MethodsA cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
29
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 33 publications
7
29
0
2
Order By: Relevance
“…The lack of difference between inflammatory marker levels for the PsA and RA cohorts when they qualified for biologics is surprising (Table ), but again reflects the criteria used to select these patients. Our study supports the observation of high ESR and CRP being predictors of MDA in bDMARD studies, as 73% of our biologics clinic PsA patients achieved MDA from a point of very active disease. This figure is higher than a Spanish real‐world cohort of 52%, two Italian cohorts of 66% and 60.3% respectively, and also exceeds that of most of the bDMARD clinical trials .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The lack of difference between inflammatory marker levels for the PsA and RA cohorts when they qualified for biologics is surprising (Table ), but again reflects the criteria used to select these patients. Our study supports the observation of high ESR and CRP being predictors of MDA in bDMARD studies, as 73% of our biologics clinic PsA patients achieved MDA from a point of very active disease. This figure is higher than a Spanish real‐world cohort of 52%, two Italian cohorts of 66% and 60.3% respectively, and also exceeds that of most of the bDMARD clinical trials .…”
Section: Discussionsupporting
confidence: 90%
“…Our study supports the observation of high ESR and CRP being predictors of MDA in bDMARD studies, as 73% of our biologics clinic PsA patients achieved MDA from a point of very active disease. This figure is higher than a Spanish real‐world cohort of 52%, two Italian cohorts of 66% and 60.3% respectively, and also exceeds that of most of the bDMARD clinical trials . This suggests that the Australian PBS criteria are specific in their selection of good responders.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Investigators in other studies did assess the burden of disease in patients fulfilling only 1 of the targets compared with those not fulfilling that target. It was shown in those studies that patients achieving the target had better scores for patient-reported outcomes compared with patients in whom the target was not achieved (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…This was a post hoc analysis of data from an observational, multicenter, cross-sectional study carried out at twenty-five rheumatology outpatient clinics in the whole of Spain [11].…”
Section: Methodsmentioning
confidence: 99%